A case study of the implementation of learning styles in two primary school classrooms : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Educational Administration at Massey University - McCallum, Jeannette Frances (Massey University, 2000)
The aim of the National Curriculum is to: Seek to raise the achievement levels of all students and to ensure that the quality of teaching and learning in New Zealand schools is of the highest international standard. (Ministry of Education, 1993) However, current assessment of children's achievement in the New Zealand education system suggests that not all children are successful learners, despite restructuring of the education system and recent curriculum reform. Educational statistics indicate the aim of the National Curriculum is not being achieved. International mathematics results from the Ministry of Education (1997) Third International Maths and Science Study, state that New Zealand has scored below the international average at Year 5 and Year 8 levels. In Ministry of Education (1996) National Education Monitoring Project, non-Maori students performed better than Maori students in all ten Reading and Speaking tasks at Year 4 and six of ten tasks at Year 8 level. Ten years after 'Tomorrow's Schools' Wylie (1999) reports that children from low-income homes and Maori children have gained least from the reforms (p. 7). It therefore seems reasonable that other options for improved student achievement need to be considered. Although there is extensive literature in the U.S.A. about the effectiveness of the Learning Styles approach, there has been little research conducted in New Zealand primary schools. This study reports on the experience of three classes of primary school children (a Year 4 and 5 class for term 4 in 1998 and two Year 3 and 4 classes in 1999) where the teachers attempted to match instruction, learning context and children's preferred learning styles. The study focuses on the following questions: 1. Does knowing one's learning style improve students' learning? 2. To what extent is learning improved when instruction and learning context matches students' learning styles? 3. What are the principal difficulties in implementing learning styles in classrooms, as perceived by teachers? The case study concludes, from the perceptions of children and teachers, that matching learning styles with instruction and learning context does improve learning, especially for those children who underachieve or who learn differently. However, the two teachers report that although they consider the learning style theory is valid and is seen to improve learning and teaching, practicalities of implementation are problematic. Implementing a new teaching methodology is not a simple process. Effective implementation of learning styles requires a paradigm shift in teachers' ideology from teacher-centred to child-centred learning. Whether this paradigm shift is possible within our current educational system, driven by 'New Right ideology' and the traditional concept of a state primary school, is discussed. The study focuses on three issues in the implementation of learning styles: the need for a paradigm shift; school culture and management structures; and, understanding how teachers develop expertise. The study suggests directions for further research, including an action research study to implement a school wide initiative to cater for students learning through their preferred learning styles. Further research could focus on the process of implementing methodological innovations through analysing the institutional setting; its structures, cultures, management styles and practices. Research that focuses on a whole school, as opposed to a single classroom, may provide insight into greater understanding of implementation of changes and achieving a paradigm shift from 'traditional' to 'modern' teaching methodologies.
Keywords: Learning, Psychology of; Cognitive styles in children; Teaching; Case studies; New Zealand